Pertussis is increasing in unimmunised infants: is a change in policy needed?. Issue 3 (1st March 1999) - Ranganathan, Sarath; Tasker, Robert; Booy, Robert; Habibi, Parviz; Nadel, Simon; Britto, Joseph
Abstract : The proportion and trend in absolute number of pertussis notifications in young infants has increased each year in England and Wales since the accelerated immunisation schedule was introduced. We report five infants all less than 3 months of age admitted with life threatening pertussis infection to two paediatric intensive care units. Despite aggressive cardiorespiratory support measures, three of the infants died. Pertussis remains a significant cause of morbidity and mortality in unimmunised infants. In this age group presentation is likely to be atypical and infection more severe. Public health measures to prevent the disease could be strengthened. Chemoprophylaxis should be offered to susceptible contacts and booster vaccinations against pertussis considered.